ARE CLINICAL MEASURES OF CERVICAL FLEXOR ENDURANCE, DIVIDED ATTENTION AND COMPUTERIZED DYNAMIC VISUAL ACUITY DIFFERENT IN ELITE YOUTH ICE HOCKEY PLAYERS WHO REPORT A PREVIOUS HISTORY OF CONCUSSION COMPARED TO THOSE WHO DO NOT?. Issue 7 (11th March 2014) - Schneider, K; Emery, CA; Kang, J; Meeuwisse, W
Abstract : Background: Concussion is a commonly encountered injury. Evaluation of clinical tests at baseline will provide insight on clinical alterations that may persist following concussion. Objective: The objective of this study was to evaluate differences in baseline measures of cervical flexor endurance (CFE), walking while talking test (WWTT) and computerized dynamic visual acuity (cDVA) in elite youth ice hockey players who do and do not report a previous history of concussion. Design: Cross-sectional study. Setting: Sport Medicine Clinic (Alberta, Canada). Participants: Bantam (12–14 years) and Midget (15–17 years) ice hockey players (n=550). Risk factor assessment: Participants completed a baseline questionnaire, including a question regarding previous history of concussion (yes/no). Main outcome measurements: Participants completed clinical tests of CFE, WWTT and cDVA at baseline. Results: Multivariate linear regression, adjusted for cluster, age group and sex was used to estimate mean differences in clinical measurement scores by concussion history (yes/no). Individuals reporting a previous history of concussion were able to hold a test of CFE for a geometric mean time of 0.88 (95% CI; 0.81–0.97) seconds less than those who did not report a previous history of concussion (P=.009). The time to complete WWTT complex compared to self-selected walking speed was a mean of 2.85 (1.09–4, 62) seconds slower in midget females with a previous history of concussion. Players reporting a previous concussion had significantly lower cDVA score at 85 degrees/second [cDVAleft =−0.036 logMAR (95%CI: −0.056, −0.016)]. Conclusion: Computerized DVA (85 degrees/second) and CFE were lower in players with a previous history of concussion. The effect of past concussion history on tasks of divided attention depended on age group and sex. These findings allow a further understanding of clinical alterations that may persist following a concussion and identify an area to target in a future clinical trial for prevention.